IMPLEMENTATION OF DISASTER RISK REDUCTION EDUCATION IN DISASTER-SAFE EDUCATIONAL UNITS: A COMPARISON OF SMAN 5 AND SMAS AL ADZKAR SOUTH TANGERANG - Jakiatin Nisa; Eko Teguh Paripurno; Yohana Noradika Maharani; Jaka Purwanta; Arif Rianto Budi Nugroho; Anissa Windarti; Eny Muryani (Universitas Sebelas Maret (UNS), 2026)
Disaster risk reduction (DRR) education is critical in disaster-prone Indonesia, including vulnerable Tangerang Selatan. Disaster-safe educational units (SPAB) aim to enhance school community preparedness, yet implementation remains suboptimal, requiring comparative school evaluations. This study compares DRR education implementation in SPAB at SMAN 5 and SMAS Al Adzkar Tangerang Selatan, focusing on the school community's preparedness level. A mixed methods approach with an explanatory sequential design was employed, involving 373 respondents (principals, teachers, students, and non-teacher staff). Quantitative data were collected via written tests and structured questionnaires, while qualitative data came from in-depth interviews and observations. The results indicate that students’ understanding of disaster threats at both schools was “Very High” (average score >3.21 out of 4), while teachers and educational staff scored “High” (average 2.41–3.20). Understanding of disaster risk among principals, teachers, and educational staff was “Medium” (average 1.00–1.07 out of 2), with students at SMAN 5 scoring “High” (1.38) and students at SMAS Al Adzkar “Medium” (1.19). The average score for understanding disaster capacity across all groups was in the “High” category. Qualitative findings reveal that the integration of disaster risk reduction materials into the curriculum remains limited to certain subjects, the development of specific disaster risk reduction teaching materials is suboptimal, and extracurricular activities at both schools are not explicitly designed as part of disaster risk reduction efforts. These results highlight the need to strengthen SPAB implementation comprehensively by enhancing preparedness, curriculum integration, instructional materials, and extracurricular programs to improve resilience in disaster-prone schools.